2019
DOI: 10.1111/1742-6723.13368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a ketamine sedation protocol on intubation rates and undesirable outcomes in the transport of patients with acute behavioural disturbance

Abstract: Objectives To identify the effects of the introduction of a ketamine sedation protocol on the rates of intubation and adverse events associated with retrieval of patients with acute behavioural disturbance. Transport of patients with acute behavioural disturbance poses clinical and logistical management difficulties, as well as risks. Remote Australian communities are separated by vast distances. Risks to aircraft and crew, and patient and community must be balanced. Ketamine has received increasing attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, the mortality associated with ketamine has generally been attributed to the condition underlying the profound agitation [35,38], and overzealous endotracheal intubation may have taken place due to unfamiliarity with the ketamine-induced, dissociated state and anticipated clinical course [39]. A recent before-and-after study in Australasia has since shown reduced rates of endotracheal intubation after introduction of ketamine in the prehospital setting [40]. Droperidol had historically been associated with torsades de pointes but has since demonstrated minimal risk of malignant tachydysrhythmia and a low overall adverse event rate in large, observational studies [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mortality associated with ketamine has generally been attributed to the condition underlying the profound agitation [35,38], and overzealous endotracheal intubation may have taken place due to unfamiliarity with the ketamine-induced, dissociated state and anticipated clinical course [39]. A recent before-and-after study in Australasia has since shown reduced rates of endotracheal intubation after introduction of ketamine in the prehospital setting [40]. Droperidol had historically been associated with torsades de pointes but has since demonstrated minimal risk of malignant tachydysrhythmia and a low overall adverse event rate in large, observational studies [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Australia and New Zealand have been studying and using ketamine on the field by paramedics for several years. They have found decreased rates in intubation and pain scores after ketamine was introduced into their protocol [10][11][12].…”
Section: Resultsmentioning
confidence: 99%